Melia dubia Progenies from Satpura and Sahyadri Ranges of South Gujarat have Potential for Salinity Tolerance - D., David Camus; Thakur, N. S.; Patel, D. P.; Gunaga, R. P.; Chauhan, R. S.; Garde, Y. A. (Indian Forester, 2025)
Rising salinity in agricultural lands threatens sustainable crop production. This study investigates salinity tolerance mechanisms in eight Melia dubia progenies from South Gujarat, India. A multi-index physiological approach + (total plant salinity tolerance, Na exclusion index, osmotic tolerance index, tissue tolerance index)was employed to assess tolerance beyond shoot fresh weight. Significant variation was observed among progenies (p < 0.05). P5, P6, P7, and P8 consistently displayed superior performance across all parameters, indicating their potential for saline environments (Between 3 dS/m to 9 dS/m). Notably, each high-performing progeny exhibited distinct tolerance strengths, suggesting diverse coping mechanisms. Future research should explore the genetic basis of these mechanisms and conduct field trials for real-world validation. This combined approach will be crucial for developing and deploying salt-tolerant M. dubia for ecological restoration.